Low-beta versus high-beta band cortico-subcortical coherence in movement inhibition and expectation - Cao, Chunyan; Litvak, Vladimir; Zhan, Shikun; Liu, Wei; Zhang, Chao; Sun, Bomin; Li, Dianyou; van Wijk, Bernadette C.M. (Neurobiology of disease, 2024)
Beta band oscillations in the sensorimotor cortex and subcortical structures, such as the subthalamic nucleus (STN) and internal pallidum (GPi), are closely linked to motor control. Recent research suggests that low-beta (14.5–23.5 Hz) and high-beta (23.5–35 Hz) cortico-STN coherence arise through distinct networks, possibly reflecting indirect and hyperdirect pathways. In this study, we sought to probe whether low- and high-beta coherence also exhibit different functional roles in facilitating and inhibiting movement. Twenty patients with Parkinson's disease who had deep brain stimulation electrodes implanted in either STN or GPi performed a classical go/nogo task while undergoing simultaneous magnetoencephalography and local field potentials recordings. Subjects' expectations were manipulated by presenting go- and nogo-trials with varying probabilities. We identified a lateral source in the sensorimotor cortex for low-beta coherence, as well as a medial source near the supplementary motor area for high-beta coherence. Task-related coherence time courses for these two sources revealed that low-beta coherence was more strongly implicated than high-beta coherence in the performance of go-trials. Accordingly, average pre-stimulus low-beta but not high-beta coherence or spectral power correlated with overall reaction time across subjects. High-beta coherence during unexpected nogo-trials was higher compared to expected nogo-trials at a relatively long latency of 3 s after stimulus presentation. Neither low- nor high-beta coherence showed a significant correlation with patients' symptom severity at baseline assessment. While low-beta cortico-subcortical coherence appears to be related to motor output, the role of high-beta coherence requires further investigation. [Display omitted] •Beta band coherence between cortex and basal ganglia consists of distinct sub-bands.•Low-beta and high-beta coherence localize to different cortical sources.•Low-beta coherence modulates with executed compared to inhibited movements.•Low-beta coherence correlates with reaction time when movements are expected.•The functional role of high-beta coherence remains speculative.